Poppy Harmon and the Pillow Talk Killer - Hollis, Lee (Hollis, Lee. Desert Flowers mysteries., 2021)
Retiree-turned-PI Poppy Harmon likes the anonymity of working behind the scenes for the hottest names in Palm Springs, but when solving a case demands dragging her old acting career out of retirement, she finds herself investigating the death of her co-star, a rising starlet with a persistent stalker.